How to use systems thinking in business decision-making - Mishra, Vinaytosh (SAGE Publications Ltd, 2025)
This guide probes into the multifaceted discipline of systems thinking, tracing its origins and evolution within the business domain. The first section provides a comprehensive introduction, defining system thinking and outlining its historical development. It highlights key principles and foundational concepts for understanding how systems thinking applies to business environments. The second section focuses on the nature of complex systems, discussing feedback loops and system dynamics that characterize such systems. It introduces causal loop diagrams for visualizing interactions, dependencies, and various systems thinking tools and techniques. The third section explores the practical application of systems thinking through systems archetypes in business analysis. The fourth section examines emerging trends and technologies, particularly the integration of artificial intelligence (AI) and machine learning with system thinking. It also discusses the concept of digital twins using system dynamics modelling and the role of system thinking in promoting sustainability and corporate social responsibility (CSR). The guide summarizes the impact of systems thinking on decision-making processes, highlighting key takeaways for businesses and researchers.